Surface‐Enhanced Raman Scattering: A Novel Ultra‐Sensitive Semiconductor SERS Substrate Boosted by the Coupled Resonance Effect (Adv. Sci. 12/2019). Issue 12 (19th June 2019) - Yang, Lili; Peng, Yusi; Yang, Yong; Liu, Jianjun; Huang, Haoliang; Yu, Bohan; Zhao, Jimin; Lu, Yalin; Huang, Zhengren; Li, Zhiyuan; Lombardi, John R.
Abstract : In article1900310, Yong Yang and co‐workers present a strategy, the "coupled resonance" effect, matching the excitation wavelength with the molecular resonance, charge transfer (CT) resonance and electromagnetic resonance of the surface‐enhanced raman scattering (SERS) substrate, to optimize the SERS performance of a new semiconductor SERS‐active substrate Ta2 O5 by energy band engineering. Furthermore, the concomitant photoinduced degradation of probed molecules in the time‐scale of SERS detection is revealed as a non‐negligible factor that limits the SERS performance of some semiconductors with photocatalytic activity.